2018
DOI: 10.3390/molecules23102425
|View full text |Cite
|
Sign up to set email alerts
|

Heterocycles 48. Synthesis, Characterization and Biological Evaluation of Imidazo[2,1-b][1,3,4]Thiadiazole Derivatives as Anti-Inflammatory Agents

Abstract: Non-steroidal anti-inflammatory drugs (NSAIDs) are an important pharmacological class of drugs used for the treatment of inflammatory diseases. They are also characterized by severe side effects, such as gastrointestinal damage, increased cardiovascular risk and renal function abnormalities. In order to synthesize new anti-inflammatory and analgesic compounds with a safer profile of side effects, a series of 2,6-diaryl-imidazo[2,1-b][1,3,4]thiadiazole derivatives 5a–l were synthesized and evaluated in vivo for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 46 publications
0
31
0
1
Order By: Relevance
“…This reaction was carried out with acetone at room temperature in the presence of a base (NaOAc, Na 2 CO 3 ). The obtained thioesters can be converted to the corresponding thiazolo [3,2-b] [1,2,4]triazoles 1 under the action of sulfuric acid, [26][27][28][29][30] acetic anhydride in acidic medium, [21,[31][32][33] PPA, [34] pTSA, [35] or POCl 3. [36] Synthesis of thiazolo [3,2-b] [1,2,4]triazoles 1 proceeds through oxidative alkylation by acid condensation and MW radiation (Scheme 1).…”
Section: Synthesis Of Thiazolo [32-b][124]triazole Derivativesmentioning
confidence: 99%
“…This reaction was carried out with acetone at room temperature in the presence of a base (NaOAc, Na 2 CO 3 ). The obtained thioesters can be converted to the corresponding thiazolo [3,2-b] [1,2,4]triazoles 1 under the action of sulfuric acid, [26][27][28][29][30] acetic anhydride in acidic medium, [21,[31][32][33] PPA, [34] pTSA, [35] or POCl 3. [36] Synthesis of thiazolo [3,2-b] [1,2,4]triazoles 1 proceeds through oxidative alkylation by acid condensation and MW radiation (Scheme 1).…”
Section: Synthesis Of Thiazolo [32-b][124]triazole Derivativesmentioning
confidence: 99%
“…In recent years, the imidazothiadiazole derivatives have been studied in depth for their wide‐ranging biological activities, as they possess antimicrobial, anticonvulsant, diuretic, anticancer, antitubercular, analgesic, and anti‐inflammatory properties. [ 14–16 ] Imidazothiadiazole derivative i (Figure 1) has been reported by Karki et al [ 17 ] to possess anticancer activity and derivative ii (Figure 1) has been reported by Kumar et al [ 18 ] as a potent tumor‐associated CA IX and XII inhibitor. Motivated by these findings, we envisioned to synthesize a novel series of imidazothiadiazole ( 5a – t ) scaffolds bearing 3‐functionalized benzenesulfonamide moiety and evaluated them for CA inhibition potential against hCA I, II, VA, and XII.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1,2 ] These compounds are having pharmaceutical [ 3 ] and biological significances [ 4 ] and huge synthetic advantages. Their therapeutic usages include anticancer, [ 5 ] antifungal, [ 6 ] antibacterial, [ 7 ] anti‐inflammatory, [ 8 ] and antioxidant. [ 9 ] They have applications in the field of veterinary products, agrochemicals, corrosion inhibitors, developers, copolymers and so on.…”
Section: Introductionmentioning
confidence: 99%